A European Voluntary Humanitarian Aid Corps: Learning from the Americans - Anne Lauenroth; Annegret Bendiek (Stiftung Wissenschaft und Politik (SWP), 2010)
Like the tsunami in Asia at the end of 2004, the earthquake in Haiti at the beginning of this year demonstrated the shortcomings of European crisis response capabilities. Drawing on the Lisbon Treaty, the responsible European Commissioner has therefore announced her intention to make a concrete proposal in the second half of the year for the rapid establishment of a European Voluntary Humanitarian Aid Corps. The design of the Corps's mandate, funding and management structure will determine its success. With 2011 earmarked as the European Year of Volunteering, the member states would be wise to enlarge the European crisis management capacities with a European Voluntary Corps modelled after the US Peace Corps
Keywords: 320